Penggunaan Bengkel Kerja Dan Pengaruhnya Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Teori Dan Praktek Pekerjaan Kosen Pintu Dan Jendela Siswa Jurusan Bangunan Di SMK - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2024)
Engineering Mechanics as one of the courses that support courses, especially civil engineering study programs, must be truly mastered by students. Lack of mastery of the field of mechanics can result in declining learning achievement in courses in the building engineering department. The purpose of this study was to determine the ability to master engineering mechanics has an influence on completing concrete construction calculations in the Civil Engineering study program. This study is a descriptive study. The sample in this study was 64 students using the Total Sampling technique, namely taking samples with the same number as the population. Data collection was carried out in the following ways: a. The ability to master engineering mechanics was obtained from the results of semester exams. b. The ability of students to complete concrete construction was obtained by using the experimental method to see from a treatment and create concrete construction questions related to material with engineering mechanics. The data analysis technique used was the statistical analysis technique with regression and correlation analysis. Data collected from 64 sample members included the ability to master engineering mechanics (X) and the ability of students to complete concrete construction (Y). The results of the study showed the degree or level of relationship between the ability to master engineering mechanics and students' ability to complete concrete construction calculations is r = 0.947. Thus the coefficient of determination r2 = 0.89, this means that 89.7% of the variations answered are also students' ability to complete concrete construction calculations determined by the ability to master engineering mechanics and the rest by other factors.